Two-year analysis of changes in the optic nerve and retina following anti-VEGF treatments in diabetic macular edema patients - Filek R (Dove Medical Press, 2019)
Richard Filek,1 Phil Hooper2,3 Tom G Sheidow2,3 John Gonder2,3 Subrata Chakrabarti,1 Cindy ML Hutnik1–31Department of Pathology and Laboratory Medicine, Western University, London, ON, Canada; 2Department of Ophthalmology, Western University, London, ON, Canada; 3Ivey Eye Institute, St. Joseph’s Health Care London, London, ON, CanadaPurpose: To evaluate long-term structural and functional changes that happen to the optic nerve and retina following ranibizumab (Lucentis) injections in diabetic macular edema (DME) patients.Methods: Patients with clinically significant DME requiring anti-VEGF injections underwent pre-injection baseline, 6, 12, and 24 month follow-up tests. The tests performed were optical coherence tomography (OCT), best-corrected visual acuity (BCVA), and visual field (VF). Wide-field fluorescein angiogram (IVFA) was performed to monitor the progression of diabetic ischemia.Results: A total of 30 patients requiring anti-VEGF injections and 21 control patients not requiring anti-VEGF injections were enrolled in the study. From baseline, the average macular thickness significantly decreased (p<0.0002) over the 24-month time period. Mean perfused ratio significantly increased (p<0.0005) at 6, 12, and 24 months. Cup volume and vertical cup-to-disk ratio significantly increased (p<0.0014) over the study period. This was verified by masked independent grading of patient optic nerve stereo-photographs by glaucoma specialists. BCVA significantly (p<0.0006) improved over the study period. VFs showed a non-significant trend of deteriorating peripheral vision at 12 and 24 months.Conclusion: Clinically, anti-VEGF therapy appears to affect the optic nerve by increasing cup volume and increasing vertical cup/disk ratio over time. The results provide a cautionary note to monitor both the retina and optic nerve status in patients undergoing frequent injections.Keywords: diabetic macular edema, retina, optic nerve, anti-VEGF, lucentis, ranibizumab